The determinants of financial literacy among chess athletes in indonesia and its relationship to financial behaviour - Syaputra, Arifa Rizki; Damayanti, Sylviana Maya (Journal of Business and Management, 2020)
Abstract. Being an athlete is not just considered as a hobby, but for some people, it is a way of life, a profession. However, the athlete in Indonesia is faced by many uncertainties; there are many cases where athletes fall into poverty after retirement. This uncomfortable uncertainties condition stacked up with the uncertainness of financial crisis that could happen anytime. Hence, it is crucial for athletes to manage their finance well. Completely aware of this situation, this research aim to analyze athlete, especially chess athletes determinants of financial literacy and the relationship to financial behaviour. The study found out that chess athletes financial literacy level is considered low in all areas of financial literacy. Meanwhile, formal education, age, monthly income and monthly spending are significant variables towards financial literacy with formal education as the most significant variable. On the other hand, overall financial literacy has significant effects towards almost all seven financial behaviour variables. From the findings, it is important for government to rethink the way they literate society regarding financial management. Government can cooperate with related department such as OJK and national sports committee to implement improved financial literacy program.Keywords: financial literacy, financial behaviour, chess athlete, athlete.